Implicações psicossociais da pobreza na permanência de estudantes de universidades públicas do Ceará - Abreu, Márcia Kelma de Alencar (2019)
The democratization policies in public higher education in Brazil, which culminated from the Quota Law in 2012, expanded the opportunities for access to historically excluded groups. Thus, it is necessary to understand what are the coping strategies and the strengthening mechanisms that poor students have been undertaking in overcoming adversities and experiences of oppression, considering that, despite them, they manage to maintain a satisfactory performance. The general objective of this thesis is to analyze how the psychosocial implications of poverty impact on the permanence of students. The research was carried out in two universities of Ceará, Federal University of Ceará (UFC) and Regional University of Cariri (URCA). A mixed research approach was used. In the quantitative stage, a sample of 251 subjects was constituted and online questionnaires were used, whose data were analyzed with descriptive statistics, analyses of variance and regression models, with the aid of SPSS software. In the qualitative stage, 8 students from both institutions participated through semi-structured interviews. Qualitative information was evaluated through analyses content with the aid of ATLAS ti 5.2 software. The quantitative sample was composed of students from several majors, 64% womans; 80% young people between 18 and 23 years, 91%; graduates of public schools, 65%; with monthly family income situated between 1 and 2 Brazilian minimum wages. The subjects interviewed belong to the Computer Engineering, Medicine, Psychology and Administration majors of UFC and Pedagogy, Law, Nursing and Production Engineering majors of URCA. The results reveal that educational and social asymmetries, directed by meritocratic ideology, make academic performance emerge as a focus. It was found that dissatisfaction with performance academic suggests higher levels of daily discrimination, lower levels of emotional balance and higher Multidimensional Poverty Index (in the dimensions of housing, health and subjective aspects). It is concluded that the student welfare policies respond to the main demands of students, such as the provision of paid scholarships and benefits, which enables the survival of those assisted. However, these policies do not cover the material needs of all, since some are excluded from the criteria of the Programs. The subjective, cultural and pedagogical dimensions are not satisfactorily addressed, since the assistance focuses on the materiality of the permanence. It was identified that poorer students experience more daily discrimination, perceive less social support and have worse rates of emotional balance. Discriminatory experiences intersect motives crossed by poverty, such as race, gender, physical appearance, socioeconomic level, sexual orientation, being a quota holder, and academic performance. It was identified that the emotional balance is shaken by experiences of discrimination, in a context of asymmetries and boundaries, triggering oppressive mechanisms, shame and humiliation. It was identified as coping mechanisms: social support; collective strategies (assertion, coping, cooperation and polarization); and individual strategies (invisibility, academic performance, participation in other training spaces). We conclude that giving visibility to the theme of poverty and its psychosocial implications is fundamental to tension the force field that sustains inequalities and asymmetries in the academic environment, enabling the effective permanence of poor and quota holders students, who seek their right to belong and remain in it.